Analisis Kesehatan Sektor Bank Digital yang Terdaftar di BEI dengan Pendekatan Risk Based Bank Rating pada Periode 2022-2024 - Iswardhani, Indri (Master Manajemen, 2025)
This study aims to analyze the health of the digital banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024 using the Risk-Based Bank Rating (RGEC) approach, which involves four main aspects: risk profile, good corporate governance, earnings, and capital. The research method used is descriptive quantitative analysis with secondary data. The sampling method was purposive sampling, which includes four digital banks listed on the IDX: ARTO (Bank Jago Tbk), BBHI (Bank Harda Internasional Tbk), BBYB (Bank Neo Commerce Tbk), and AMAR (Bank Amar Indonesia Tbk). The results show that based on the composite value calculations, these digital banks have shown significant improvement, moving from a composite rating of 3 (PK-3) with a "fairly healthy" predicate in 2022 to a composite rating of 2 (PK-2) with a "healthy" predicate in 2023 and 2024. Although improvements have been made in several key areas, such as risk management and profitability, the main challenges still faced by digital banks are liquidity management and credit quality, reflected in the high Loan to Deposit Ratio (LDR) and significant Non-Performing Loans (NPL). This study also emphasizes the importance of strengthening good corporate governance (GCG) principles and more effective risk management to support the sustainability and growth of the digital banking sector in Indonesia. Therefore, digital banks need to focus more on improving liquidity management, credit quality, and enhancing the efficiency of margin and capital management to overcome future challenges and strengthen their position in the digital banking industry.